The Ecological Other : Environmental Exclusion in American Culture - Ray, Sarah Jaquette (Book collections on Project MUSE., 2013)
In this book, the author examines the ways in which environmentalism can create social injustice through discourses of the body. The author argues that the expression of environmental disgust toward certain kinds of bodies draws problematic lines between ecological "subjects" - those who are good for and belong in nature - and ecological "others" - those who are threats to or out of place in nature. Ultimately, this book urges readers to be more critical of how they use nature as a tool of social control and to be careful about the ways in which they construct arguments to ensure its protection.